Antihypoxic, anti-ischemic and acute toxicity effect of Salvia leriifolia Benth. root in mice and rats - Hossein Hosseinzadeh; Alireza Khoei; Mahmoodreza Jafari; Javad Ghasamipour (Institue of Medicinal Plants, ACECR, 2002)
The antihypoxic effect Salvia leriifolia root aqueous and ethanolic extracts was studied using hypoxia creating in a tightly glass container in mice. Ischemia was induced using four-vessel occlusion model and evaluated by optical and transmission electrinic microscope in rats. The extract of S. leriifolia showed antihypoxic effect and the minimum effective dose was 0.7 g/kg. In ischemic rat, the aqueous and ethanolic extracts significantly reduced neural cell injury in CA1 and CA3, 4 hippocampus rats. LD50 values (i.p, mice) of the aqueous and the ethanolic extracts were 1.45 g/kg and 1.55 g/kg, respectively. Both extracts comprised saponins and tannins. These results indincate that the extracts of S. leriifolia root have protective effect against hypoxia and ischemia.